The course of biochemical processes in fermenting-forming aggregate - Zarubina, Victoria; Arsenieva, Larisa; Smirnova, Elizabeth (НУХТ, 2012)
It was investigated the dynamics of sugars in the dough and changes in fractional composition of protein substances in semi-finished products under the influence of higher pressure that is created in the chamber of fermenting-forming aggregate.
Keywords: higher pressure; biochemical processes; fermenting-forming aggregate; cold extrusion; підвищений тиск; біохімічні процеси; бродильно-формувальний агрегат; холодна екструзія; повышенное давление; биохимические процессы; бродильно-формующий агрегат; холодная экструзия; кафедра експертизи харчових продуктів; кафедра іноземних мов професійного спрямування